2018
DOI: 10.5897/err2018.3603
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of the studies in the field of mathematics education

Abstract: The purpose of this study is to perform bibliometric analysis of the scientific researches published in mathematics education subject area between 1980 and 2018, to find out the general layout of the scientific knowledge and communication structure of the field using an objective method, driven from the data. The publications were analyzed according to publication year, type of publication, language of publication, title of publication, name of the author, country of the author and number of citations taken fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…The data collection process for this scoping review followed a systematic and rigorous approach to ensure the reliability and replicability of the study. The criteria used to select the articles to be analyzed were clearly defined to maintain the quality of both the analysis and the selected articles (Hemingway & Brereton, 2009;Moule & Goodman, 2009;Özkaya, 2018). To identify relevant articles, we focused on publications from reputable sources such as Springer, Taylor & Francis, Elsevier, and SAGE, which are known for their high-quality content in the field of STEM education.…”
Section: Data Collection Processmentioning
confidence: 99%
“…The data collection process for this scoping review followed a systematic and rigorous approach to ensure the reliability and replicability of the study. The criteria used to select the articles to be analyzed were clearly defined to maintain the quality of both the analysis and the selected articles (Hemingway & Brereton, 2009;Moule & Goodman, 2009;Özkaya, 2018). To identify relevant articles, we focused on publications from reputable sources such as Springer, Taylor & Francis, Elsevier, and SAGE, which are known for their high-quality content in the field of STEM education.…”
Section: Data Collection Processmentioning
confidence: 99%
“…Beyer, C. J., Delgado, C., Davis, E. A., & Krajcik, J. (2009) (Aksu & Güzeller, 2019;Demir & Selvi, 2018;Demirgil, 2018;Doğru vd., 2019;Liu vd., 2011;Özkaya, 2019;Yu vd., 2016 (Aksu & Güzeller, 2019;Doğru vd., 2019;Gil-Doménech vd., 2020;Jiménez-Fanjul vd., 2013;Nebioğlu, 2019;Nebioğlu & Kalıpçı, 2020;Özkaya, 2018;Yu vd., 2016).…”
Section: Konu Kümelenmelerimentioning
confidence: 99%
“…Ülkelerin alandaki atıf patlama değerlerine bakıldığında ise İngiltere'nin en fazla atıf patlama değerine sahip ülke olduğu, Güney Kore'nin de yakın zamanda alanda söz sahibi ülkeler arasına girdiği sonucu ortaya çıkmıştır. Güzeller, 2019;Doğru vd., 2019;Gil-Doménech vd., 2020;Jiménez-Fanjul vd., 2013;Nebioğlu, 2019;Nebioğlu & Kalıpçı, 2020;Özkaya, 2018;Yu vd., 2016).…”
Section: Konu Kümelenmeleriunclassified
“…A literature review showed that bibliometric studies on mathematics education were present (Fanjul et al, 2013;Hwang & Tu, 2020;Özkaya, 2018), but bibliometric study in the field of geometry teaching was not found. Therefore, the aim of the study was to examine the articles indexed in SSCI and ESCI (2015ESCI ( -2020 in relation to the "geometry teaching and learning area" by the bibliometric analysis method.…”
Section: Introductionmentioning
confidence: 99%